1990
DOI: 10.1093/carcin/11.4.617
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hypolipidemic drugs nafenopin and clofibrate on phenotypic expression and cell death (apoptosis) in altered foci of rat liver

Abstract: Phenotypically altered liver foci were produced in female Wistar rats by a single dose of N-nitrosomorpholine followed by promotion with phenobarbital (PB) for 20 or 28 weeks. Then treatment was changed to either hexachlorocyclohexane (HCH), or cyproterone acetate (CPA), or nafenopin (Naf) or clofibrate (Clof), two hypolipidemic drugs. Foci were identified by a positive reaction for gamma-glutamyl-transpeptidase (GGT) and other cytological markers. HCH and CPA could substitute for PB as foci promoters; in cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
2
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 0 publications
0
12
2
1
Order By: Relevance
“…However these studies have either used different PP (6,41), or significantly different dosing regimens (14). Although no statistically significant effects on apoptosis as assessed by caspase-3 immunohistochemistry were seen in the present study, an analysis of the liver pathology data identified an increase in the number of apoptotic bodies primarily in the centrilobular area in the 800 mg/kg/day dose group (Figure 1).…”
Section: In Vivo and Postmortem Studycontrasting
confidence: 57%
See 2 more Smart Citations
“…However these studies have either used different PP (6,41), or significantly different dosing regimens (14). Although no statistically significant effects on apoptosis as assessed by caspase-3 immunohistochemistry were seen in the present study, an analysis of the liver pathology data identified an increase in the number of apoptotic bodies primarily in the centrilobular area in the 800 mg/kg/day dose group (Figure 1).…”
Section: In Vivo and Postmortem Studycontrasting
confidence: 57%
“…Along with PP-mediated hepatocellular proliferation, suppression of apoptosis by PP both in vitro and in vivo has been reported (6,14,41). However these studies have either used different PP (6,41), or significantly different dosing regimens (14).…”
Section: In Vivo and Postmortem Studymentioning
confidence: 99%
See 1 more Smart Citation
“…In adult animals, apoptosis acts as a safeguard to prevent cells with damaged DNA from progressing to a tumor. Several studies have shown that agonists of PPARα, including DEHP, suppress rates of apoptosis in rat and mouse liver in vivo [105,106,31]. Thus, it was hypothesized that the cells that would normally be removed by apoptosis may then persist for further mitogenic stimulation by non-genotoxic carcinogens, giving rise to tumors.…”
Section: Suppression Of Apoptosismentioning
confidence: 99%
“…34 Pek çok çalışmada fare ve sıçan karaciğerinde PPAR-α agonistlerinin in vivo olarak apoptozu baskıladıkları belirlenmiş-tir. 35,36 Ftalatlara temas sonrası normal olarak apoptozla uzaklaştırılan hücrelerin mitojenik stimülasyonla canlı kaldığı ve bölündüğü rapor edilmiştir. PPAR-α agonistleriyle yapılan bir çalış-mada, yalnızca orta (50 haftalık) ve ileri yaşlarda (100 haftalık) olan hayvanların karaciğerlerinin bu etkiye hassas olduğu, genç hayvanların karaciğer-lerinde bu etkinin görülmediği bildirilmiştir.…”
unclassified